Evaluation of Stability of 5- Fluorouracil under Different Stress Conditions: High Performance Liquid Chromatography and Infrared Spectroscopic Approach - Yadav, Nisha; Singh, Parul; Mehrotra, Ranjana (Current Pharmaceutical Analysis, 2012)
5-fluorouracil is one of the most widely used chemotherapeutic agents for the treatment of several types of cancer. The present study describes the determination of stability of 5-fluorouracil under different stress conditions using high performance liquid chromatography (HPLC) and infrared (IR) spectroscopy. The separation of 5-fluorouracil was carried out on a C18 reverse phase column using 40 mM KH2PO4 as mobile phase. The ultraviolet detection wavelength was 260 nm. The HPLC method was validated and the response of the drug was linear in the concentration range of 20 μg ml-1 to 550 μg ml-1 with a correlation coefficient of 0.9995. The % R.S.D. values for intra-day and inter-day precision were determined as <0.2% and <1% respectively. Infrared spectroscopic measurements were carried out in diffuse reflectance and attenuated total reflectance (ATR) modes. The study reveals that 5-flurouracil shows mild degradation up to 275°C and major degradation at about 285°C. It undergoes a degradation of about 22% when exposed to stress conditions of acidic hydrolysis. A major degradation of about 97% was observed under alkaline condition. The drug undergoes degradation from 26% to 41% when exposed to oxidative condition. The drug remains stable when exposed to UV irradiations.
Keywords: Diffuse reflectance